MAWROSE Animal Clinic Management System - Roslee, Nurain; BIN MOHD NAWI, NAZRI (Applied Information Technology And Computer Science, 2026)
The veterinary industry is advancing, necessitating modern management systems to improve service quality in animal clinics. Currently, MAWROSE Anima Clinic uses Kreloses, a cloud-based system. Still, it has limitations such as flexibility in customization, reliance of software updates, and a lack of customer engagement features. This project aims to develop an enhanced MAWROSE Animal Clinic Management System to address these issues by introducing a customer portal and flexible system customization. The portal enables customers to manage appointments, access their pet’s health records, and use features like pet adoption and cat hotel reservation services. The system was designed using an object-oriented and web-based approach, using tools like HTML, CSS, JavaScript, and MySQL to implement and maintain the database. Key findings indicate that the proposed system improves operational efficiency, improves customer satisfaction, and aligns better with clinic workflows. Future work could explore integrating with mobile application and incorporating artificial intelligence for predictive analytics, such as detecting common health issues in pets based on medical records. This project highlights the potential of technology in solving real-world challenges, benefiting both clinics and their clients in reducing the dependency on clinic staff for routine tasks.